House price index as an alternative pricing benchmark for Islamic home financing: evidence of Malaysia - Redzuan, Nur Harena; Kassim, Salina (2015)
The pricing benchmark is usually used as a guide to calculate the rate of return of the financing. In the case of Malaysia, it is not known whether residential property values have significant relationship with the general performance of the economy. We propose that the house price index to be a viable benchmark of the real values of property to determine the price of Islamic home financing product. This study compares two models; the existing pricing benchmark which relies on interest rate and the alternative pricing benchmark which relies on the house price index. It examines the long-run relationship of the two benchmark rates with selected macroeconomics variables. By comparing the interest-based benchmark with the non-interest benchmark, this study attempts to highlight the sensitivity of the two benchmarks to the real economic conditions. Focusing on quarterly data covering the period from 2001 to 2014. The study finds that the non-interest benchmark, House Price Index have significant long-run relationships with the macroeconomic variables. It shows that this alternative benchmark has the connection to the economic movements that lead to the stability of the non-interest financing instruments. The findings of this study would provide important insights on the viability of the Housin g Price Index as the alternatives to benchmark of the Islamic financing home financing product. This study contributes to the empirical evidence for the feasibility of adopting interest-free benchmark to price Islamic home financing product.